Enhancing Productivity and Production Hygiene in a Tofu Factory in Kp. Cijambe, Cikarang Selatan District as a Form of Micro, Small, and Medium Enterprises (MSMEs) in the Creative Economy - Rismawati; Putri, Zakiyah; Rambe, Fitria Rahmadani; Citra, Dela Yulia; Aisyah, Aprilia Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted in the household tofu production industry located in Kp. Cijambe, RT/RW 011/005, Desa Sukadami, Kecamatan Cikarang Selatan, Kabupaten Bekasi. Its objectives were to enhance productivity and hygiene standards in the tofu production process and to provide better understanding of business management to tofu artisans. The approach involved direct mentoring through training in the implementation of hygienic standard operating procedures (SOP), the use of personal protective equipment, and the optimization of production processes by reorganizing equipment layout and improving raw material efficiency. The findings demonstrated a 30% increase in productivity and significant improvements in hygiene standards within the production area through consistent sanitation of equipment and the work environment. This implementation proved that focused training and structured business management can enhance the quality of tofu production. Continued training and independent business management are recommended to sustain the achieved production standards.